2019
DOI: 10.3390/met9050487
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Honing Angle and Roughness Height on the Tribological Performance of CuNiCr Iron Liner

Abstract: This work investigated the effect of honing morphologies of CuNiCr iron liner on its tribological properties sliding against the Cr-Al2O3 coated piston ring. The worn surface morphology and elements distribution as well as the wear behaviors of CuNiCr iron liner were analyzed to explore the influencing of the honing angle and roughness height on the friction and wear resistance. The results show that the optimized honing angle and roughness can improve the tribological performance of the iron liner, and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The machine can provide a 30 mm reciprocating stroke. The reciprocating speed can be adjusted between 0.01 and 1 m/s, and the temperature ranges from 30 to 300 °C [23].…”
Section: Wear and Friction Testsmentioning
confidence: 99%
“…The machine can provide a 30 mm reciprocating stroke. The reciprocating speed can be adjusted between 0.01 and 1 m/s, and the temperature ranges from 30 to 300 °C [23].…”
Section: Wear and Friction Testsmentioning
confidence: 99%
“…The surface roughness of BP cylinder liner is 0.4 µm (R a ), and the hardness is 170 HV 0.1 . The two liners were cut into 40 equal portions along the circumference (the central angle of the actual liner is about 9°, the arc length is 10 mm, and the length of cylinder liner specimen is 44 mm) [40].…”
Section: Friction Pairsmentioning
confidence: 99%
“…Buj-Corral et al [8] investigated the effect of abrasive density on process parameters and concluded that the oilstone density was selected according to the acoustic emission of the grinding. The authors of [9][10][11] investigated the application of honing techniques in hardened steel, CuNiCr copper-nickel alloy, analyzed the effects of honing angle and abrasive size on roughness and residual stress, and finally obtained the optimized process parameters. Muratov and Muratov et al [12] studied the honing technology of 95Cr18 and 12CrNi3N hydraulic components, analyzed the effect of honing track mesh density on surface roughness, and determined the control mechanism of mesh density.…”
Section: Introductionmentioning
confidence: 99%